An analytical model of inter-organizational relationships in project environment: A social network perspective - Samira Fallah; Naser Shams Gharneh (Tourism & Management Studies)
To fulfill a project, there are varieties of organizations cooperating as a supply chain. Being in large numbers and diversity, the supply chain may result in complexity and uncertainty in managing the projects; although it provides the required resources to achieve project objectives. The more a project faces complexity, the higher attention is required to effective management of its inter-organizational relationship model. In the following study, the structure of relations between organizations in two Iranian petrochemical projects is studied and compared. Modeling methods and analysis are based on Social Network Analysis (SNA). After modeling the network structure of each project, the inter-organizational relationships model are analyzed and compared to the ideal model of Iranian National Petrochemical Company (NPC) and the results are presented. Finally some areas for further research are also discussed.